Mini-review on an engineering approach towards the selection of transition metal complex-based catalysts for photocatalytic H2 production. Issue 11 (30th April 2019) - Huo, Jingpei; Zhang, Yu-Bang; Zou, Wan-Ying; Hu, Xiaohong; Deng, Qianjun; Chen, Dongchu
Abstract : Advances in transition-metal (Ru, Co, Cu, and Fe) complex-based catalysts since 2000 are briefly summarized in terms of catalyst selection and application for photocatalytic H2 evolution. Abstract : Among numerous metal complexes, transition metal (Ru, Co, Cu, and Fe)-based complexes exhibit rich structure types, outstanding stability and interesting properties. Advances in these transition metal complex-based molecular catalysts since 2000 can be briefly summarized from two aspects: catalyst selection and application for photocatalytic H2 evolution.